Income Support Policies for Single Parents in Europe and the United States: What Works Best?. (July 2022) - Aerts, Elise; Marx, Ive; Parolin, Zachary
Poverty rates among single parents vary considerably across countries, in part reflecting differences in the generosity and design of minimum income protections. We ask what the optimal ways are to target income support to single parents, if the prime objective of policy is to shelter those households from poverty. We map minimum income provisions for working and nonworking single-parent households across Europe and the United States, showing that three things matter for adequate minimum income protection. First, minimum wage levels matter, obviously for working single parents, but also for jobless ones since they effectively set the 'glass ceiling' for out-of-work benefits. Second, the overall generosity of the child benefit package is crucial to shelter both working and jobless single parents from poverty. Third, countries that employ a strategy of "targeting within universalism" (that is directing extra support to vulnerable groups such as single parents within the context of a universal benefit program) tend to do best.